ANALISIS PEMAHAMAN KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL PADA GURU IPS DI KECAMATAN BAWEN KABUPATEN SEMARANG (Universitas Negeri Semarang, 2020)
The study aims to analyze the understanding of pedagogic and professional competence of social studies teachers in Bawen District, Semarang Regency. The results of the analysis show that pedagogical and professional competence is not fully understood due to several constraints. Pedagogical competency constraints include; (1) the frequency of meeting and emotional closeness, (2) the number of teachers, (3) the ability of human resources, (4) the readiness of students, (5) the burden of multiple subjects, (6) less effective communication, (7) preparation of evaluation procedures not , (8) low willpower. While professional competency constraints include; (1) educational background is irrelevant, (2) readiness of students, (3) motivation to learn, (4) lack of willpower, (5) HR ability. The school seeks to develop teacher competencies, among others through the IHT (In House Training) program including training in the use of instructional media, training in writing scientific papers, training in the preparation of learning tools, etc. Penelitian bertujuan untuk menganalisis pemahaman kompetensi pedagogik dan profesional guru IPS di Kecamatan Bawen Kabupaten Semarang. Hasil analisis menunjukan bahwa kompetensi pedagogik dan profesional belum dipahami secara maksimal karena beberapa faktor kendala. Kendala kompetensi pedagogik meliputi; (1) frekuensi bertemu dan kedekatan emosional, (2) jumlah guru, (3) kemampuan SDM, (4) kesiapan peserta didik, (5) beban mata pelajaran ganda, (6) komunikasi kurang efektif, (7) penyusunan evaluasi tidak prosedural, (8) rendahnya kemauan. Sedangkan kendala kompetensi profesional meliputi; (1) latar belakang pendidikan tidak relevan, (2) kesiapan peserta didik, (3) motivasi belajar, (4) rendahnya kemauan, (5) kemampuan SDM. Pihak sekolah berupaya untuk mengembangkan kompetensi guru antara lain melalui program IHT (In House Training) meliputi pelatihan penggunaan media pembelajaran, pelatihan penulisan karya ilmiah, pelatihan penyusunan perangkat pembelajaran dsb.